2023
DOI: 10.1038/s41467-023-40422-7
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of translational decoding by m6A modification of mRNA

Abstract: N6-methyladenosine (m6A) is an abundant, dynamic mRNA modification that regulates key steps of cellular mRNA metabolism. m6A in the mRNA coding regions inhibits translation elongation. Here, we show how m6A modulates decoding in the bacterial translation system using a combination of rapid kinetics, smFRET and single-particle cryo-EM. We show that, while the modification does not impair the initial binding of aminoacyl-tRNA to the ribosome, in the presence of m6A fewer ribosomes complete the decoding process d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 69 publications
(168 reference statements)
0
2
0
Order By: Relevance
“…However, there is evidence that m6A may also enhance translation [5]. The impact of these modifications depends on multiple factors, including the presence of specific m6A reader proteins and the location of m6A on the mRNA [5,[26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is evidence that m6A may also enhance translation [5]. The impact of these modifications depends on multiple factors, including the presence of specific m6A reader proteins and the location of m6A on the mRNA [5,[26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…stability and enhancing the tRNA drop-off. This consequently results in a smaller number of ribosomes that complete the decoding process, resulting in a less efficient translation of the affected transcripts (Jain et al, 2023).…”
Section: Site-specific Deposition Of M 6 a Modifications On Nascent R...mentioning
confidence: 99%
“…Another study recently confirmed these findings by showing that m 6 A does not prevent canonical codon–anticodon base-pairing but favors alternative conformations leading to a lower stability and enhancing the tRNA drop-off. This consequently results in a smaller number of ribosomes that complete the decoding process, resulting in a less efficient translation of the affected transcripts ( Jain et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…While the syn orientation is energetically preferred in the free nucleosides and in single-stranded RNA, formation of a standard Watson–Crick base pair requires the methyl group to rotate into the anti conformation. Thus, m 6 A influences local structures and base pairing kinetics, which in turn affect global RNA folding, structures, and associated functions. Multiple studies have shown that m 6 A modulates the fate of mRNAs by influencing their stability, translation efficiency, and splicing through direct or indirect interaction with proteins. ,,, A group of direct m 6 A reader proteins each contain the YTH domain, which forms a hydrophobic binding pocket for m 6 A. Well-established human m 6 A readers include the proteins YTHDF1/DF2/DF3 and YTHDC1/DC2 . Although these YTH-domain containing proteins seem to bind m 6 A-containing RNA via similar mechanisms, they cause different downstream effects. , Interestingly, m 6 A can be reverted to adenosine through oxidative demethylation by the human m 6 A demethylase enzymes FTO and ALKBH5 .…”
Section: Introductionmentioning
confidence: 99%